ProWritingAid as AI-Powered Writing Tools: The Performance in Checking Grammar and Spelling of Students’ Writing - Fitria, Tira Nur (Politeknik Negeri Padang, 2023)
This research simulates the use of ProWritingAid as an AI-Powered writing tool for checking the grammar and spelling of English writing. This research uses descriptive qualitative. The analysis shows that in using ProWriting, visit https://prowritingaid.com/. On the homepage, several menus appear both Login and Sign up. On the left side, the displays Get Started (it's free) for the free version, and Purchase for the pro/premium version. If we don't have an account, we need to register an account with Google, Facebook, and Single Sign On (SSO). We can register with an email and enter a password. We need to fill in several questions including